Examining the role of Islamic higher education legal aid organizations in realizing justice through legal aid - Budi Sastra Panjaitan (Institute Of computer Science (IOCS), 2026)
While equal access to justice is a fundamental human entitlement, the marginalized poor still face immense barriers in securing it. Within Islamic Higher Education Institutions (PTAI), University Legal Aid Centers (OBH PTAI) are mandated to bridge this gap, translating the Islamic principle of mutual assistance (al-mu'awanah) into academic community service. However, prior research heavily centers on the abstract theological and normative value of these campus clinics, leaving a critical gap in assessing their operational performance. To address this omission, this study employs a statute approach (pendekatan perundang-undangan) alongside a conceptual framework. This legal approach allows for a rigorous examination of the prevailing laws, government regulations, and institutional mandates that govern legal aid delivery in Indonesia. By analyzing these statutory frameworks, the study evaluates how OBH PTAIs.The final analysis uncovers a sharp. Even though OBH PTAIs bear identical statutory weights and legal responsibilities under the law as other formal legal aid organizations, their actual, real-world contributions to dismantling injustice for disenfranchised communities remain heavily constrained and underutilized.